THEMATIC CURRICULUM ANALYSIS USING CONTEXT, INPUT, PROCESS AND PRODUCT EVALUATION MODELS - Sapuadi, Sapuadi; Sulistyowati, Sulistyowati; Syahmidi, Syahmidi; Rizal, Setria Utama; Hikmah, Nurul; Mualimin, Mualimin (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This study aimed to determine how the readiness of grade IV and V teachers in thematic learning planning in SD / MI in Central Kalimantan. This research used descriptive qualitative methods. Data collection techniques through interviews, observation, and documentation. The research was conducted in 7 schools spread across 1 city and 2 districts in Central Kalimantan. Data analysis techniques using Miles and Huberman with data validation techniques triangulation techniques. The results of this study showed that in the context through needs analysis, it is known that the curriculum used by 5 schools is the Thematic curriculum, while the other 2 schools use the Merdeka curriculum. As for the preparation oflesson plan(RPP) learning tools, it was done in teams by the teacher concerned, the input obtained is learning tools, along with materials, teaching materials, methods, and learning strategies. As for the learning process of the Thematic curriculum, 70% is carried out by permapel, and the resulting product is a form of final assessment using digital madrasa report(RDM) anddigital report application(ARD).The implication of this study was to provide an evaluation of the use of the CIPP Model (Context, Input, Process, Product) model, so that it can be a reference to develop and have an impact on improving the quality of learning through the right model in learning, especially in thematic learning.